1977
DOI: 10.1111/j.1365-2389.1977.tb02264.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Adsorption by Illinois Soils

Abstract: ourteen surface and 6 subsurface horizons of' Illinois soils adsorbed significant amounts of 1;-with release of OH -. At low concentrations, adsorption was described by both Langmuir and Freundlich isotherms. The calculated Langmuir adsorption capacities were related to pH, clay, organic carbon, and amorphous aluminum contents.Two soils with different gross chemical properties behaved in essentially the same manner, with adsorption maxima occuring between pH 5.5 and 6.5. The similarity between adsorption at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
41
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(43 citation statements)
references
References 15 publications
2
41
0
Order By: Relevance
“…Studies have shown that F adsorption is accompanied by OH release from the mineral surface supporting the theory that the process involves ligand exchange with a coordinated OH group (Bower and Hatcher l96j; Omueti and Jones 1977). The amount of OH released through F adsorption has been positively correlated with the release of Al from various phyllosilicates and amorphous aluminum hydroxides suggesting degradation of the mineral structure (Huang and Jackson 1965;Perrott et al 1976).…”
mentioning
confidence: 63%
See 3 more Smart Citations
“…Studies have shown that F adsorption is accompanied by OH release from the mineral surface supporting the theory that the process involves ligand exchange with a coordinated OH group (Bower and Hatcher l96j; Omueti and Jones 1977). The amount of OH released through F adsorption has been positively correlated with the release of Al from various phyllosilicates and amorphous aluminum hydroxides suggesting degradation of the mineral structure (Huang and Jackson 1965;Perrott et al 1976).…”
mentioning
confidence: 63%
“…Montmorillonite adsorption of F is highest near pH 6, whereas kaolinite adsorption decreases linearly from pH 3 to 7 (Omueti and Jones 1977).In general, kaolinite tends to adsorb more F than montmorillonite (Bar-yosef et al 1988).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…This has long been recognized by analysts because aluminium interference has to be avoided or eliminated by various means during determination of fluoride. Fluorine-aluminium complexes have received most attention in relation to soil (Bower & Hatcher, 1967;Omueti & Jones, 1977;Davison, 1983) and, more recently, in connection with acidification of fresh water (Driscoll, et al, 1980;Johnson et al, 1981). Where plants are concerned, Hani (1978) reported that when fluoride was added to an acid sandy loam, both it and aluminium increased in solution and this led to an increase in both elements in the leaves of maize, hi an investigation of species of the Theaceae that accumulate high concentrations of fluoride from 'normal' soils, Davison (1983) and Davison, Takmaz-Nisancioglu & Bailey (1985) found that they also contained high concentrations of aluminium.…”
Section: Introductionmentioning
confidence: 99%